Intellectual capital and performance of small and medium audit practices The interactive effects of professionalism - Kigongo Kaawaase, Twaha; Bananuka, Juma; Kwizina, Thomson Peter; Nabaweesi, Jennifer (Journal of Accounting in Emerging Economies, 2019)
The purpose of this paper is to examine the interactive effects of professionalism in the relationship between intellectual capital (IC) and performance of small and medium audit practices (SMPs) within the context of a developing economy, Uganda. Design/methodology/approach – Data were collected through a questionnaire survey of 77 SMPs registered with the Institute of Certified Public Accountants of Uganda through their managing partners. The authors utilized multiple regression analysis to test hypotheses using centered variables and an interaction term between IC and professionalism. Findings – IC is a significant determinant of performance of SMPs in Uganda; while professionalism when acting alone is not significant, however, results have shown that professionalism interacts with IC to enhance performance of SMPs. Research limitations/implications – This study, owing to the absence of publically available published financial statements of SMPs, utilizes a questionnaire to collect data on performance of SMPs which could be less objective. Further, as the study is limited to SMPs in Uganda, it is possible that the results are only applicable to Uganda’s accountancy field. In addition, the use of multiple regression is prone to problems associated with sampling error. However, the likelihood of these problems is mitigated by the interface with data and regression analysis diagnostics that were carried out. Originality/value – This study provides initial empirical evidence on the relationship between IC, professionalism and performance of SMPs in developing economies. The study further indicates that while IC acts independently to influence firm performance, its interaction with professionalism enhances this performance
Keywords: Intellectual capital; Professionalism; Uganda; Performance; Resource based view and dynamic capabilities; Small and medium audit practices